Constructing Whiteness in Dating Applications: A Case of Expatriate Tinder Users in Indonesia - Mustikawati, Sinta Dwi (KnE Social Sciences, 2019)
While many white expatriates from Euro-American countries living and working in Indonesia intend to live in Indonesia for the long term, they are often considered (and consider themselves) as the ‘others’. As a consequence, they never feel fully accepted as members of the society in Indonesia albeit their efforts to adapt their lives there, hence their difficulties in developing their relationships with Indonesian people. One way for them to build relationships with Indonesians is through dating practices. However, they are often restrained within the conventional dating scene in Indonesia. With the emergence of mobile dating applications such as Tinder, these dating practices can be mediated by new media prior to their face-to-face interactions with their dates. For expatriates who seek dates with Indonesian people, this mediated experience creates a digital space for them to present themselves in the dating scene in Indonesia. This paper thus aims to see how their cultural identities play a role for them to express themselves through Tinder with other users in Indonesia both in online and offline worlds. Using observations and interviews of four expatriates in Indonesia, this paper shows that Tinder allows them to express their cultural identities in the digital world in order to have an alternative dating scene in Indonesia. Keywords: cultural identity; dating application; Tinder